OVERVIEW OF SELF-CARE BEHAVIOR IN PATIENTS WITH TYPE II DIABETES MELLITUS : LITERATURE REVIEW - Umam, Khotibul; Yusuf, Ah; Iswatun, Iswatun (Universitas Airlangga, 2023)
Introduction: Diabetes Mellitus is a chronic disease that requires self-care to improve the quality of life and reduce the occurrence of complications. Self-care behaviors that can be applied by DM patients include physical activity, diet regulation, control of blood glucose levels, treatment, and prevention of complications. The purpose of this literature review is to describe self-care behavior in Type II Diabetes Mellitus patients. Methods: Literature Review using the PICOT framework from several databases (Scopus, Science Direct, Google Scholar, Research Gate and Pubmed). The search results are displayed in the PRISMA. Abstracts and full articles were assessed for eligibility (n = 34), The articles correspond to research feasibility in quantitative studies (n = 12). Results: After collecting data, all data were selected according to the inclusion. Based on a review article, the self-care regimen for type 2 Diabetes Mellitus patients generally includes physical activity, diet, controlling blood glucose levels, monitoring blood glucose and medication. However, most of the respondents compliance with self-care management behavior in type 2 Diabetes Mellitus (DM) patients has not been carried out optimally. Conclusions: The role of nurses is important in increasing adherence to self-care behavior in Diabetes Mellitus patients.